Implementation of Forest Rights Act 2006 in Protected Areas of Odisha - Sarangi, Tapas Kumar (Indian Forester, 2016)
In protected areas, natural resources support the livelihood needs of local communities, but human activity affects wildlife survival and biodiversity conservation, and leads to serious human animal conflict, such as crop raiding, livestock predation, and loss of human life. Therefore, the future of wildlife is always in conflict with the livelihood of communities. The Forest Rights Act (FRA), 2006 recognises the basic livelihood rights of forest dwellers, but its implementation is besieged with several problems at various institutional levels. With special reference to the implementation of the Forest Rights Act, 2006 in protected areas of Odisha, this paper discusses the conflict between concepts of conservation and livelihood of people, and suggests some ways to strengthen livelihoods.